Human Ovarian Tissue Cryopreservation as Fertility Reserve - Albani, Elena; Bracone, Graziella; Biccari, Sonia Di; Vitobello, Domenico; Fattizzi, Nicola; Levi-Setti, Paolo Emanuele (IntechOpen, 2012)
None